Oxidative Stability of Cottonseed Butter Products under Accelerated Storage Conditions - Zhongqi He; Sunghyun Nam; K. Thomas Klasson (Molecules, 2023)
Cottonseed is a natural product of cotton (Gossypium spp.) crops. This work evaluated the oxidative stability of cottonseed butters through accelerated autoxidation by storage at 60 °C for 25 days. Three oxidative stability parameter values (peroxide value, p-anisidine value, and total oxidation value) were monitored over the storage time. These chemical measurements revealed that the storage stability of the butter products was dominated by primary oxidation of lipid (oil) components, while the secondary oxidation levels were relatively unchanged over the storage time. An analysis of the tocopherols (natural oxidants in cottonseed) suggested not only the protection function of the molecules against oxidation of the cottonseed butter during storage, but also the dynamic mechanism against the primary oxidation of lipid components. Attenuated total reflectance–Fourier-transform infrared spectroscopy (ATR–FTIR) data confirmed no changes in the major C functional groups of cottonseed butters over the storage time. On the other hand, characteristic minor peaks of conjugated dienes and trienes related to lipid oxidation were impacted by the accelerated storage. As each day of accelerated oxidation at 60 °C is equivalent to 16 days of storage at 20 °C, observations in this work should have reflected the oxidative stability behaviors of the cottonseed butters after about 13 months of shelf storage under ambient storage conditions. Thus, these data that were collected under the accelerated oxidation testing would be useful not only to create a better understanding of the autooxidation mechanism of lipid molecules in cottonseed butters, but also in developing or recommending appropriate storage conditions for cottonseed end products to prevent them from quality degradation.